From CD16a Biology to Antibody-Dependent Cell-Mediated Cytotoxicity Improvement - Coënon, Loïs; Villalba, Martin (Frontiers in Immunology, 2022)
Antibody-dependent cell cytotoxicity (ADCC) is a potent cytotoxic mechanism that is mainly mediated in humans by Natural Killer (NK) cells. ADCC mediates the clinical benefit of several widely used cytolytic monoclonal antibodies (mAbs) and increasing its efficacy would improve cancer immunotherapy. CD16a is a receptor for the Fc portion of IgGs and is responsible to trigger NK cell-mediated ADCC. The knowledge of the mechanism of action of CD16a gave rise to several strategies to improve ADCC, either by working on the mAbs or the NK cell. In this review, we give an overview of CD16a biology and describe the latest strategies employed to improve antibody-dependent NK cell cytotoxicity.